Comparison Study of Polylactic Acid on Tensile Properties and Water Absorption - Suleiman, Nazrul Hazmie; AHMAD, MAZATUSZIHA (Progress in Engineering Application and Technology, 2024)
These study discuss on the effect of water absorption and printing orientation on the tensile properties of Poly-lactic Acid. PLA is one of the widely used material in 3D printing due to its biodegradable and recyclable nature. Usually PLA is use in making prototype or early designing tester for showcase before the actually product which will need the understanding of the properties of PLA in different situation. Thus tensile test and water absorption test are used to test the capability of the PLA model (Standard ASTM D638 type-IV) to withstand pulling force after immerse in water for a duration of days. The method that was used for water absorption is to immerse the sample in water completely for the duration of days that was set early on which are 0, 2, 4, 8 and 16 days. Also for the tensile test, the rate of pulling by the UTM is at 5mm/min. With the data obtained from the testing, the study found that the PLA model after being immersed in water has the capability to withstand pulling force after reaching the cracking point of the PLA. This show that without any treatment the PLA will break when reaching its breaking point instantly and with any treatment or mixing, the capability of PLA in any situation may improve with its properties. As for further research, different temperature of immersion or different type of liquid is used for immersed can be explored in finding the best treatment that can improve the PLA properties.